Relationship Between National Income, Institutional Change and Outbound Tourism Based on Panel Data of the G20 from 1995 to 2014 - Gongwei, Wang (Journal of landscape research, 2017)
Based on panel data of 17 economies in the G20 from 1995 to 2014,this paper,in terms of the total samples,developed countries and developing countries,explored the impact of national income on outbound tourism and the moderating effect of institutional change on the relationship between national income and outbound tourism.The results showed that:(1)for the total samples,developed countries and developing countries,national income had a positive impact on outbound tourism;(2)for the total samples and developing countries,institutional change had a positive moderating effect on national income and outbound tourism,indicating that with the deepening of marketization,the facilitating role of national income on outbound tourism strengthened;(3)for developed countries,institutional change had a negative moderating effect on national income and outbound tourism,indicating that with the deepening of marketization,the facilitating role of national income on outbound tourism weakened.